Immune Therapies - Munshi, Nikhil C. (2007)
Incidents of cancer, particularly in elderly patients living in developing countries, are predicted to raise significantly as the general population rises to an estimated 8.9 billion by the year 2050. Immune cells with specific functions and abilities to localize are vital to cancer prevention. Incidents of multiple myeloma, which is caused by transformed plasma cells, will increase in the coming decades. Combinational treatments prolong the survival of myeloma patients, in turn, escalating the management costs. Even though there have been many accomplishments made in the areas of immune cells and the biology of myeloma, there are still many obstacles in the way of conceptualizing the inter-relationships between immune cells and tumor cells. In order to provide better understanding of these concepts and to move towards improved therapies for myeloma, cell-based therapeutic approaches should be developed. In the following chapter, we will attempt to further illuminate these processes and concepts.